PEMBERDAYAAN KADER PKK DAN REMAJA BERBASIS ASET LOKAL DALAM UPAYA PENCEGAHAN PERKAWINAN ANAK DI DESA JOMBANG KABUPATEN JEMBER - Titin Nurhidayati; Rofiatul Hosna; M. Nafiur Rofiq; Fahmi Ziyyad Alafthoni; Umi Salamah; Rahmat (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service program aims to empower PKK cadres and adolescents as agents of change in preventing child marriage. The program applied the Asset Based Community Development (ABCD) approach by leveraging local assets such as PKK cadres, teachers, and community leaders. Activities included training, mentoring, reproductive health education, character development, and peer-to-peer education practices designed in a participatory manner. The results showed increased knowledge and awareness among adolescents, the formation of peer cadres actively delivering education, and improved capacity of PKK cadres in assisting the community. In addition, strong collaboration was established with schools, community leaders, and the village government to ensure program sustainability. These findings highlight that empowering PKK cadres and adolescents through the ABCD approach is effective in reducing child marriage practices and can be replicated in other regions.